EFEKTIVITAS PEMBELAJARAN KETERAMPILAN MENULIS MENGGUNAKAN METODE WIDYAWISATA PADA SISWA KELAS VI SDN TUNGGAK KABUPATEN SERANG - Eka Nurul Mualimah; Sri Purwantiningsih; DC Aryadi (STKIP Setiabudhi, 2023)
In this study, we used test instruments to obtain data on the results of learning to write poetry in SDN Tunggak, Serang Regency using the field trip method. Learning planning greatly affects the success of learning objectives by applying the Field Trip method. The learning objectives of writing poetry are designed in process activities in the form of: idea discovery, poetry writing, presentation, and assessment of learning are considered effective because almost all aspects are categorized as good. The implementation of learning to write poetry by students is very creative, diligent, seriously enthusiastic, active, conscientious, and cooperation is an indicator of success. The use of the word into a poem is very effective, because students are given the freedom to work. Learning to write poetry, the evaluation results are also declared effective because the average student score acquisition reaches the expected value standard based on the aspects studied, namely themes, diction, and mandates, is declared effective judging from the posttest results higher than the prettest score.